HOW DOES VITAMIN D SUPPLEMENTATION CHANGE THE OUTCOME FOR MOTHER AND CHILD? - Nikolai Lazarov; Faisal Saghir (Peytchinski Publishing, 2024)
Introduction: Pregnancy represents a period in which rapid bodily changes occur, which include a wide range of physiological interactions occurring in both the mother and the developing foetus. The role of vitamin D3 metabolism within pregnancy is an over-shadowed but very important aspect for the normal and healthy muscoskeletal development of the foetus and for the various alternative functions associated with vitamin D3 for the pregnant female. The purpose: To provide a detailed understanding ofhe current status of vitamin D3 and the role it has within pregnancy and to identify the efficacy and the wide range of effects that vitamin D3 has for both the mother and foetus. Materials and methods: We conducted a review of the available literature at PubMed, Google Scholar, and Science Direct, which included observational studies, prospective and controlled trials, reports and guidelines for appropriate dosages of vitamin D3 to be used within pregnant females. Results and Discussion: Our review of the scientific literature showed evidence of the benefits of vitamin D3 within pregnant women and the effect, if any, on the numerous physiological processes taking place within both the mother and the foetus. We found data indicating that vitamin D3 can prove to be very important in preventingreeclampsia, gestational diabetes and congenital malformations of the foetus. Conclusion: The administration of vitamin D3 may be a potential technique to prevent complications to the mother and the developing foetus both during and after pregnancy, either solely or as a combined therapy.